Deletion and Point Mutations of PTHLH Cause Brachydactyly Type E - Klopocki, Eva (Elsevier, 2010)
Autosomal-dominant brachydactyly type E (BDE) is a congenital limb malformation characterized by small hands and feet predominantly as a result of shortened metacarpals and metatarsals. In a large pedigree with BDE, short stature, and learning disabilities, we detected a microdeletion of ∼900 kb encompassing PTHLH, the gene coding for parathyroid hormone related protein (PTHRP). PTHRP is known to regulate the balance between chondrocyte proliferation and the onset of hypertrophic differentiation during endochondral bone development. Inactivation of Pthrp in mice results in short-limbed dwarfism because of premature differentiation of chondrocyte. On the basis of our initial finding, we tested further individuals with BDE and short stature for mutations in PTHLH. We identified two missense (L44P and L60P), a nonstop (X178WextX(∗)54), and a nonsense (K120X) mutation. The missense mutation L60P was tested in chicken micromass culture with the replication-competent avian sarcoma leukosis virus retroviral expression system and was shown to result in a loss of function. Thus, loss-of-function mutations in PTHLH cause BDE with short stature.